Gerechtigkeit und Gleichheit - Ladwig, Bernd (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2000)
The author defends an egalitarian conception of justice against recent anti-egalitarian criticisms in politics and philosophy. On a conceptual level he argues that modern morality is based on a principle of equal respect and concern. As a consequence, all that a conception of distributive justice has to elaborate is an adequate interpretation of equality. In short, equality is the epitome of justice. The article gives an outline of a conception that respects and accentuates the responsibility of persons for leading their own lives and that nevertheless justifies strong demands for redistribution in the realm of social politics.